Online Learning in the 21st Century: Perspectives from the University of Port Harcourt, Nigeria - I. E. Yarhere; I. O. Obuzor; E. Fomsi (Issues and Development in Health Research Vol. 6, 2021)
Schools in Nigeria were shut down, and lectures stopped altogether at the peak of the COVID 19 pandemic. The capacity of the Nigerian educational environment to carry out online interactions may be stretched thin with many foreseeable challenges. Objectives: To identify the current familiarity and use of online classroom platforms by medical students and Paediatric residents and identify the barriers to its use for medical education. Methods: A descriptive comparative study design using a semi-structured online questionnaire Google survey of 128 medical students and residents in training in University of Port Harcourt Teaching Hospital assessing demographics, availability of online learning tools, and application. Results: Both groups had high familiarity but low use of Google classroom and preferred mobile devices to laptops. There was high familiarity 90.6%, but low use 42.2%, of Google classroom and the ease of using Google classroom for interfacing or interacting between learners and facilitators was affected by Internet availability, Pearson correlation, 0.185, p = 0.037, but not electric power availability, Pearson correlation, 0.135, p = 0.133. Conclusions: There is an overall high awareness of a range of the Google classroom LMS platforms by medical students and residents. However, constant electric energy supply, availability of the internet, and competence in preparing multimedia presentations and uploading these for assessment may enhance the use of online learning platforms in Nigeria for undergraduate and postgraduate medical education. For online learning to continue without hindrance, the learners must motivate the facilitators by turning in their assignments early.